Perceived Effectiveness of the Anti-Smoking Public Service Advertisement on YouTube (#SuaraTanpaRokok) - Rizanna Rosemary; Novi Susilawati; Deni Yanuar; Nur Anisah; Mawaddah Idris (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M) Institut Bisnis dan Komunikasi LSPR, 2021)
Indonesia’s tobacco control law enforcement remains weak and has not regulated the total ban on tobacco advertisement, promotion, and sponsorship bans (TAPS). Meanwhile, mediated anti-smoking messages have been significantly found to reduce smoking prevalence in many countries, helping people to stop smoking and preventing new smokers. Unfortunately, the anti-smoking Public Service Advertisements (PSAs) in Indonesia is unable to compete with the extensive and creative cigarette advertising or pro-smoking messages in many media platforms. Messages encouraging people to stop smoking and delivering the hazardous effects of smoking remain spotty in terms of numbers and visibility, leaving people with limited information about the adverse effects of smoking. There has been little research literature looking at how people perceived the effectiveness of anti-smoking messages. This study aims to identify and assess the anti-smoking PSAs by #suaratanparokok. A content analysis is carried out to examine the perceived effectiveness of the #suaratanparokok PSAs on YouTube. The involvement of YouTube influencers and optimizing social media platforms are important in delivering the PSAs. This study provides insights and recommendations to warn people about the danger of smoking through effective anti-smoking messages.